Quinoxaline as a corrosion inhibitor for copper in nitric acid: Kinetics, statistical, and theoretical investigations - Adiba A. Mahmmod; Anees A. Khadom; Abdul Amir H. Kadhum; A. Alamiery (Case Studies in Chemical and Environmental Engineering)
In the present work, quinoxaline (0.002 M) as a corrosion inhibitor for copper in 1.5 M HNO3 has been investigated at different temperatures. Weight loss, regression, and density functional theory (DFT) were used in the experimental, mathematical, and quantum chemical studies, respectively. Experimental studies show that the corrosion rate of copper increases with temperature, according to the Arrhenius equation. On the other hand, the percentage of inhibitor efficiency increased as temperature decreased, approaching a maximum value of 91 % at 25 °C. Kinetic studies showed that the corrosion reaction was zero-order. Corrosion rate data was fitted to a second-order mathematical model with a 0.974 correlation coefficient. The effect of inhibitor concentration on the corrosion rate was studied at low and high levels of temperature. The corrosion rate decreases with an increase in an increase in inhibitor concentration. The adsorption on the copper surface was spontaneous and followed the Langmuir adsorption isotherm. The theoretical quantum chemical calculation was used to support the experimental study. These calculations showed that the inhibitor molecules were the donors of electrons, while the metal surface was the acceptor. In addition, Mulliken charge data showed that the negative charges of quinoxaline are mainly concentrated on the nitrogen and carbon atoms. On the other hand, all hydrogen atoms have positive charges. This indicates a lack of hydrogen bond formation with the copper surface. This extensive study not only confirms quinoxaline’s efficacy as a corrosion inhibitor but also advances our knowledge of how it interacts with copper, opening the way to the creation of more focused and effective corrosion inhibitors that follow the rules of molecular design.